A prospective study between carbamazepine, phenytoin and sodium valproate as monotherapy in previously untreated and recently diagnosed patients with epilepsy. Issue 7 (July 1985) - Callaghan, N; Kenny, R A; O'Neill, B; Crowley, M; Goggin, T
Abstract : One hundred and eighty one patients with previously untreated epilepsy were randomised to sodium valproate, phenytoin or carbamazepine as monotherapy and followed up for a median period which ranged from 14 to 24 months. All three drugs were highly effective in the control of generalised seizures but less effective for partial seizures. Excellent or good control was achieved with therapeutic levels of sodium valproate and carbamazepine, but with subtherapeutic levels of phenytoin.